Risk factors of self-medication in pregnant women: a study of non-steroidal Anti-inflammatory drugs (Research, Society and Development, 2021)
Objective: To analyze the potential risks to pregnant women and fetuses caused by self-medication of non-steroidal anti-inflammatory drugs. Methods: The proposed methodology for this research follows a strategy of literature review, exploratory and descriptive research, whose collection was carried out in different databases, such as Scientific Electronic Library Online (SCIELO), records from both the Virtual Health Library (BVS), and records of the Medical Literature Analysis and Retrievel System Online (MEDLINE/PUBMED). The search took place through the use of the descriptors “SELF MEDICATION”; “PREGNANT”, “AINES” and “RISKS”. Results: It was noticed that the use of medication during pregnancy through the practice of self-medication with Ibuprofen 9 (27%), Dipyrone 6 (18%), Bromopride 2 (6%), Paracetamol 13 (40%), Dimenhydrinate 3 (9 %), being 31 (94%) in the form of tablets was reported by 27 (33.75%) pregnant women, and 3 (11.1%) who had complaints of use such as headache, emesis and nausea and the indication was reported by 2 (6%) pregnant by the mother and the others on their own. Conclusion: After analyzing several scientific articles, what is very clear is that the use of non-steroidal anti-inflammatory drugs in early pregnancy has not shown to be a risk factor, however, after the first trimester it can be fatal, both for the occurrence of congenital structural malformations in the fetus, as for kidney problems. When it comes to the mother, it is clear that NSAIDs can prolong her delivery time, cause hemorrhages and weaken her eggs for future reproduction.